1967
DOI: 10.1097/00006254-196706000-00038
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomy and Histology of Xo Human Embryos and Fetuses

Abstract: Thirteen abortuses with a known chromosomal complement of 45 (XO) were collected. Of these, eight contained an embryo or fetus ranging in age from five weeks to four months. Various gross anatomical abnormalities were evident in the four larger specimens and these included horseshoe kidney, unicornate uterus, single umbilical artery and cystic hygroma. One specimen had bilateral cystic hygromata. In all specimens, the gross anatomical appearance of the gonad was normal and, when examined histologically, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0
1

Year Published

1986
1986
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 0 publications
4
97
0
1
Order By: Relevance
“…Turner's syndrome is a genetic disorder in which the ovaries are apparently normal at birth and then prematurely lose their function early in childhood (8). As a result of this gonadal dysgenesis, the children lack ovarian estrogen and androgen production, usually do not undergo spontaneous pubertal maturation and, in most cases, are infertile.…”
Section: Discussionmentioning
confidence: 99%
“…Turner's syndrome is a genetic disorder in which the ovaries are apparently normal at birth and then prematurely lose their function early in childhood (8). As a result of this gonadal dysgenesis, the children lack ovarian estrogen and androgen production, usually do not undergo spontaneous pubertal maturation and, in most cases, are infertile.…”
Section: Discussionmentioning
confidence: 99%
“…Forty years ago ovaries from fetuses with TS with the 45,X complement were shown to have a normal germ cell count until week 18 of gestation, after which they seemed to undergo accelerated degeneration (10)(11). The gonadal insufficiency is associated with high levels of follicle-stimulating hormone (FSH) and luteinizing hormone (LH) in early childhood (2-5 years) and after the time of normal onset of puberty (11 years), while during the neonatal period and late childhood the level of FSH and LH is comparable to those in healthy girls (12).…”
Section: The Pituitary Ovarian Axismentioning
confidence: 99%
“…In the 1960s Singh and Carr, and Carr et al studying ovaries from fetuses with TS with the 45,X complement, showed that the germ cell count seemed normal until week 18 of gestation, after which accelerated degeneration occurred (33,34). Speed suggested that the infertility associated with TS was due to this loss of germ cells, and that it was initiated by the inability of the lone X chromosome to pair with an autosome during meiosis (35).…”
Section: Morphologymentioning
confidence: 99%